Comprehensive Reconstruction of Facial Defects: A Case Study Utilizing Combined Skin Flap Techniques and Composite Graft Chondrocutaneus - Reksoprawiro, Sunarto; Lumintang, Nico; Tandililing, Sherly; Papea, Melky Rendy (PT. Publikasiku Academic Solution, 2025)
Post-operative defects of skin tumor removal in the facial area, especially the nasal area, are very common. Reconstruction of defects in the nasal, presents a great challenge for surgeons where the presence of asymmetric conditions, changes in skin color and texture will be easily visible and cause changes in facial shape. In addition, to maintain and restore the function of the defective part that will be reconstructed, it requires high precision and expertise to obtain good results aesthetically and functionally. In this article, we present 3 cases of the combined use of auricular chondrocutaneous composite graft and paramedian forehead flap in defect reconstruction full tickness nasal ala after tumor excision. Two cases were unilateral reconstruction and 1 other case was bilateral reconstruction. Previously, the patient had been educated about the choice of surgical technique, risks and benefits of the surgical technique to be used and the patient had agreed to it. The reconstruction results in all three cases showed excellent results both aesthetically and functionally. The shape and contour of the thin auricular cartilage are very suitable for forming the nasal ala without the need for surgical molding as in other cartilage graft donors. The thin skin attached to the cartilage not only forms liningwhich is perfect but also forms a wide nostril space. The weakness of the auricular chondrocutaneous composite graft in terms of vascularization supply can be overcome with paramedian forehead flap, which is also a large skin donor with contours and skin color that are most similar to the skin of the nasal. This procedure provides excellent results in terms of aesthetics and functionality, as well as minimal complications and donor mobility, so it can be the procedure of choice for reconstruction of large defects in the nasal after tumor removal.